Studies for implementation of Neozygites floridana as control agent of two-spotted spider mite in strawberry - Duarte, Vanessa da Silveira (2013)
Neozygites floridana is an important natural enemy of Tetranychus urticae in many crops, including strawberry. In this crop there has been some changes in the production system from open field to low tunnel. This new system presents benefits to strawberry production, moreover this system increases problems with spider mites and some fungal plant pathogens; consequently increasing the use of pesticides. In order to integrate N. floridana in the management of spider mites in strawberry there are still many important aspects to be revealed on the biology, epizootiology of the fungus and the effect of crop systems on its prevalence in the field. For this, three studies were performed, being the first one about the effect of strawberry production systems (low tunnel and open field) and pesticide application on population dynamics of two-spotted spider mite T. urticae, its natural enemies (N. floridana and predatory mites), and plant diseases, the experiment was performed in Inconfidentes-MG. The population of T. urticae attained the highest level in treatments with chemical control of pest, independently of the crop system, low tunnel or open field. The fungus N. floridana was observed late in both crop seasons, in treatments with and without inoculative releases, and has suggested that it might be a natural occurrence of the fungus. The highest prevalence of the fungus were observed in treatments with high densities of T. urticae. The predatory mites occurred naturally during the two crop seasons, and the most abundant species was Neoseiulus anonymus (Chant) (57.5%). The incidence of fungal plant diseases are greater in the open field than in low tunnel, however it seems that the crop system do not affect the new disease \"vermelhao\". The second study aimed to reveal the abiotic and biotic factors involved in the regulation of resting spores formation in the hosts T. urticae and T. evansi. The Brazilian isolate ESALQ1420 produced a large number of resting spores (51.5%) in T. urticae at a temperature 11 °C, photoperiod of 10L:14D, light intensity of 42-46 (?mol m-2s-1), on non-senescent plants. Small percentages of mites with resting spores (0-5 %) were found for the Norwegian isolate NCRI271/04 under the conditions tested, and very low percentages of resting spores (up to 1%) were observed in T. evansi infected by the Brazilian isolate ESALQ1421.The third study was therefore conducted phylogenetic analysis of isolates of N. floridana and develops efficient real-time PCR-based analysis for detection and quantification of N. floridana propagules from the soil. The phylogenic three showed that Neozygites is a fungal group far from other Entomophthoromycota and that N. floridana present high intra-specific variability. This data indicates that the isolates from different Tetranychus species may be in fact different Neozygites species, not described yet. We developed a real-time PCR probe for detection and quantification of N. floridana in the soil. This molecular probe was successful in quantifying N. floridana at relatively high DNA concentrations seeded into the soil.